Characteristics of Mathematical Reversible Thinking in Junior High School Students - Aneu - Pebrianti; Suhendra Suhendra; Elah Nurlaelah; Dadang Juandi (Universitas Syiah Kuala, 2023)
Reversible thinking is a mathematical competency that influences students' success in solving problems. Problem-solving is the core of mathematics education. This research aims to identify the characteristics of students' thinking in solving problems that require reversible thinking ability. A qualitative method with a case study approach was used in this research. The study used tests and interviews on 44 eighth-grade students in West Java, Indonesia. In-depth interviews were conducted with representative students whose answers were representative of the other students. All students' answers were analyzed using the thematic analysis software ATLAS.ti. According to the characteristic indicators of reversible thinking. This study found that junior high school students' ability in reversible thinking is not optimal. Some students who successfully solve problems are limited to using backward thinking processes rather than invertible ones. The other students still have difficulties constructing answers due to the limited context when students first learn the concept (problems with forward-thinking). Thus, this ability needs to be understood by students as one factor that supports the success of the problem-solving process.